A Framework for Compiling and Reviewing Management Textbooks with a Practical and Skill-Building Approach (Comparative Case Study: Organizational Behavior Management Textbooks) - Mohammad Sheikhzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the serious harms of management education in Iran is the weakness of the content of textbooks and the lack of attention to the practical dimension and skill-building in writing them. The purpose of this article is to review and compare management textbooks in the field of organizational behavior at home and abroad. After reviewing various books on organizational behavior that are taught in management schools in the country and abroad, four common textbook titles , two domestic book titles from SAMT Publication and two foreign book titles from McGrawHill Higher Education Publication were selected. Then by using the comparative case study method, the similarity and difference of these four books were analyzed and compared based on appearance and content indicators. The research findings show that the two domestic textbooks are mainly written with a theoretical approach and their content is not up to date, while the two foreign textbooks are compiled with a practical and skill-building approach and have flexible, up-to-date and integrated content. Then, the content of one of these books (as a benchmark) was examined in more detail. Finally, a framework for compiling and reviewing management textbooks in Iran was presented.